The cake bible - Beranbaum, Rose Levy (W. Morrow, 1988)
Providing countless solutions and tips for commonly encountered baking problems, this comprehensive cake cookbook provides precise instructions for baking and decorating spectacular special-occasion cakes of any size up to eighteen inches in diameter.